CONSTRUCT AND FACE VALIDITY OF THE EYESI INDIRECT OPHTHALMOSCOPE SIMULATOR. Issue 10 (October 2017) - Chou, Jonathan; Kosowsky, Tova; Payal, Abhishek R.; Gonzalez Gonzalez, Luis A.; Daly, Mary K.
Abstract : Purpose: To evaluate construct and face validity of the Eyesi Binocular Indirect Ophthalmoscope Simulator. Methods: The performance of 25 medical students (Group A) was compared with that of 17 ophthalmology and optometry trainees (Group B) on the Eyesi Binocular Indirect Ophthalmoscope Simulator. During the course of a single session, each participant viewed an orientation module followed by an instruction session and a demonstration case, and performed 6 cases of progressively increasing difficulty (4 levels) and a 10-question face validity questionnaire. Outcomes included total score, total examination time, percent retina examined, and duration of eye exposure to light. Results: Group B achieved significantly better total scores than Group A on all difficulty levels ( P = 0.02, P = 0.001, P = 0.001, and P = 0.0001, for Levels 1–4, respectively) and had a significantly faster mean duration of examination (8 minutes 58 seconds vs. 5 minutes 21 seconds, P < 0.0001). Medical students reported higher scores in the face validity questionnaire for the simulator experience being helpful at orienting them to true indirect ophthalmology, and that further training on the simulator would improve their skills in the clinic ( P = 0.03 for all). Conclusion: The Eyesi Binocular Indirect Ophthalmoscope Simulator has significant construct and face validity and shows promise for medical education. Abstract : Supplemental Digital Content is Available in the Text.The indirect ophthalmoscopy examination is one of the most challenging examinations for novice trainees. This study provides construct and face validity of the Eyesi Indirect Ophthalmoscope Simulator and shows it as a useful tool for students of varying expertise.